Evaluation of the Dental Avulsion Knowledge Levels of Physicians Working in the Emergency Departments of Hospitals - Eskibağlar, Büşra Karaağaç; Aslan, Elif; Ayna, Buket (My University, 2023)
Objective: The aim of this study is to determine the dental avulsion knowledge levels of physicians from all specialties working in the emergency departments of hospitals, to evaluate their attitudes and behaviors, and to increase their awareness of the subject of dental avulsion through the information brochure given at the end of the survey. Material and Method: An online survey consisting of 21 questions and four sections was administered to physicians, asking questions about their personal information, their demographic information, their attitudes towards dental avulsion cases, and their knowledge of and experience with dental avulsion. The survey was administered to 152 volunteer physicians who worked in the emergency departments of 13 different hospitals in Diyarbakır city center and who had agreed to participate in the study. The Shapiro-Wilk test for conformity to normal distribution, the Kruskal-Wallis H test and the Mann-Whitney U test were used to examine differences between groups. The statistical significance level was taken as p <0,05. Results: The knowledge scores were found to be statistically significantly higher for emergency medicine specialists compared to interns, for physicians who were aware of the trauma guide compared to those who were not, and for physicians whose family members included a dentist compared to those whose family members did not include a dentist. Conclusion: According to the results of this study, it was concluded that continuous training programs are necessary to increase the knowledge and awareness levels of physicians in all branches working in emergency services about traumatic dental injuries.
Keywords: Dental Avulsion; Traumatic Dental Injures; Emergency Physicians